ANALYTICAL METHOD VALIDATION OF BENZENE USING HIGH PERFORMANCE LIQUID CHROMATOGRAPHY IN BEVERAGE CONTAINING SODIUM BENZOATE AND ASCORBIC ACID - Melania Perwitasari; Endang Lukitaningsih; Sudibyo Martono (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2014)
Abstract: Several countries reported discovering benzene in beverages containing benzoic acidand ascorbic acid. Benzoic acid decarboxylation by ascorbic acid will form benzene. AmericanBeverage Association (ABA) recommended the use of accelerated testing to test benzene inbeverages. High Performance Liquid Chromatography (HPLC) is one of several methods toanalyze benzene in a wide variety of samples, but there is no much information providedregarding the validation of analysis method of benzene. Therefore, developing analysis methodof benzene and its validation becomes a current need. The HPLC system consists of Hitachi L-2130 pump, sample injector with 20 L sample loop, and UV detector L-2420 operating at 205nm. The analytical column is a LiChrosorb Phenomenex RP-18 (250 x 4 mm, 10 m, 100 ?), themobile phase is acetonitrile:aquabidest (60:40 v/v) and pumped at a flow rate of 0,8 mL/min.Benzene separated from the matrix and follows the validation requirements. The developedanalytical method showed that resolution was 8.37, r = 0.995 with LOD and LOQ 6.52 ppb and19.75 ppb, with a precise of ?11% and recovery of 80-110%. Accelerated testing indicated thatbenzene levels increased with increasing of the temperature. Beverages containing 400 mg/mL ofascorbic acid and benzoic acid formed benzene which was detected as 699.38 ppb at 25 oC,799.61 ppb at 40 oC, and 808.94 ppb at 60 oC in 48 hours. In conclusion, the method was fullyvalidated and can be utilized to analyze benzene in beverages with the accelerated testing at 60 oC in 48 hours, so that benefits the producers and consumers in the end.Keywords : benzene, HPLC, validation method, ascorbic acid, benzoic acid